Are You Moving Up or Falling Short? An Inquiry of Skills-based Variation in Self-perceived Employability among Norwegian Employees. (April 2018) - Drange, Ida; Bernstrøm, Vilde Hoff; Mamelund, Svenn-Erik
This article investigates how educational level, job-related skills and employers' support for competence development jointly determine Norwegian employees' expectations of maintaining employment and career advancement. The data were collected in 2010 and 2013, and they comprise a representative sample of Norwegian employees. In contrast to previous research on self-perceived employability, this study divides expectations of advancement and continued employment. The results show that these are different measures of labour market success. While education is significantly correlated with both measures, the employer's support for competence development is important for expectations of career advancement, especially among the highly educated, whereas the job–skills match is most relevant for the expectation of maintaining employment.